2021
DOI: 10.3389/fnbot.2021.699174
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of EMG Pattern Recognition Model Performance in Repeated Uses by Combining Feature Selection and Incremental Transfer Learning

Abstract: Electromyography (EMG) pattern recognition is one of the widely used methods to control the rehabilitation robots and prostheses. However, the changes in the distribution of EMG data due to electrodes shifting results in classification decline, which hinders its clinical application in repeated uses. Adaptive learning can solve this problem but takes additional time. To address this, an efficient scheme is developed by comparing the performance of 12 combinations of three feature selection methods [no feature … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 34 publications
0
25
0
Order By: Relevance
“…The feature extraction of sEMG signals is a key step in the classification of hand movements based on sEMG signals [ 40 ]. In this work, four features are extracted from the sub-band signals obtained by decomposing the sEMG signal by WPT to classify hand movements [ 41 , 42 ]. These features were selected on the basis of previous studies that showed their usefulness in distinguishing hand movements based on sEMG signals [ 2 , 43 ].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The feature extraction of sEMG signals is a key step in the classification of hand movements based on sEMG signals [ 40 ]. In this work, four features are extracted from the sub-band signals obtained by decomposing the sEMG signal by WPT to classify hand movements [ 41 , 42 ]. These features were selected on the basis of previous studies that showed their usefulness in distinguishing hand movements based on sEMG signals [ 2 , 43 ].…”
Section: Methodsmentioning
confidence: 99%
“…Feature extraction is to convert the sEMG signal into a compact and information-rich feature space. The sEMG signal feature extraction methods are generally divided into time-domain (TD) features and frequency-domain (FD) features [ 41 ]. The TD feature is the TD statistics obtained by directly performing statistical analysis on the signal amplitude [ 42 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Following that, a specific tool can be chosen based on the system's requirements and characteristics. One of the most widely used pattern detection methods in myoelectric signals is support vector machines (SVM), which discover an n-dimensional hyperplane that can divide a set of extracted input features into different classes [71].…”
Section: Pattern Classificationmentioning
confidence: 99%
“…A self-collected dataset similar to the article [10] was used in this study. There are ten healthy subjects in this dataset and each individual was selected for 7 signal acquisition points in the upper limb, which could be seen as Figure 3(a): the anterior deltoid, middle deltoid, posterior deltoid, biceps, triceps, brachioradialis and flexor muscles.…”
Section: Experiments 31 Datasetsmentioning
confidence: 99%